Oracle8 troubleshooting - Velpuri, Rama.; Adkoli, Anand (Berkeley, California : Osborne McGraw-Hill, 1999)
Oracle is the world's #1 software for enterprise information management. DBAs will want to know what to look out for with Oracle 8--and they'll trust Oracle Press to give them the best information available. Fully updated for version 8, including coverage of Oracle Financials and Web Server. Contains expert insider information direct from Oracle professionals on everything from installing to system failures. Bonus CD-ROM contains World Wide Customer Support White papers and other valuable support material.
Preventive maintenance on MS Windows 3.1; preventive maintenance on MS Windows 95; preventive maintenance on MS Windows NT; preventive maintenance on Solaris; preventive maintenance on UNIX; preventive maintenance on OpenVMS; problem solving RDBMS; problem solving connectivity issues; problem solving Developer/2000; interacting with Oracle precompilers; network computing and NCA; Web application server; introduction to Oracle applications. (Part contents)
Includes index.
Keywords: ORACLE (COMPUTER FILE)